2020
DOI: 10.3390/ijerph17176187
|View full text |Cite
|
Sign up to set email alerts
|

Body Composition, Physical Activity, and Convenience Food Consumption among Asian American Youth: 2011–2018 NHANES

Abstract: The primary purpose of this study was to describe obesity, body composition, convenience food consumption, physical activity, and muscle strength among Asian American youth compared to other racial/ethnic groups. The secondary purpose was to examine whether obesity, body composition, convenience food consumption, physical activity, and muscle strength differed by acculturation levels among Asian American youth. A secondary analysis was conducted using data from 12,763 children aged 2 to 17 years that participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Among the multiple DXA assessments collected between age 18 and 23 years, the latest assessment was used as the adulthood adiposity measure. Based on sex-and age-specific FMI percentile references [31], adulthood FMI ≥ 75th percentile was considered as excess body fat [32].…”
Section: Dual-energy X-ray Absorptiometry (Dxa)mentioning
confidence: 99%
“…Among the multiple DXA assessments collected between age 18 and 23 years, the latest assessment was used as the adulthood adiposity measure. Based on sex-and age-specific FMI percentile references [31], adulthood FMI ≥ 75th percentile was considered as excess body fat [32].…”
Section: Dual-energy X-ray Absorptiometry (Dxa)mentioning
confidence: 99%
“…It has been shown that there is a positive correlation between obesity and acculturation, with adolescents who have assimilated or been highly integrated into the dominant culture being more likely to adopt food habits such as increased fast food, SSBs, and other EDNP foods [35][36][37][38], which are linked to higher rates of obesity and related co-morbidities. Furthermore, a recent comprehensive secondary analysis of the National Health and Nutrition Examination Survey (NHANES) has suggested that, as they become more acculturated, Asian American youth are more likely to frequently consume fast food [39]. Moreover, gender differences were noted, with acculturated Asian American boys, unlike girls, more likely to be obese.…”
Section: Discussionmentioning
confidence: 99%
“…3 Addressing co-occurrence behavior change for chronic disease can also have a direct effect on other key behavioral issues if the interventions are culturally tailored to the population being served. 6 Future research should focus on capturing students across a longitudinal basis to assess whether they stay within the classes identified in this study or if there are other factors that cause them to move to other latent classes. School Health, school districts, and individual schools can create policies to collect longitudinal data on students from K-12, thereby reducing the racial/ethnic gap in data representation, allowing equitable distribution of resources for research in underserved school districts.…”
Section: Implications For School Health Policy Practice and Equitymentioning
confidence: 99%
“…[6][7][8] Studies have identified differences in chronic disease predictors, such as obesity between racial/ethnic groups, sex, education level, and socioeconomic status for children and adults. 4,6,8 Ethnic minority high school students may be further marginalized given the potential for tumultuous experiences in adolescence and the potential for limited access to resources that may contribute to the prevention or management of these chronic disease predictors. Many argue that the reasons behind these racial/ethnic differences between adolescents are largely unknown and widely overlooked, as the effects of predictors typically manifest in adulthood.…”
mentioning
confidence: 99%
See 1 more Smart Citation